FINANCIAL INCLUSION AS A DRIVER FOR ECONOMIC GROWTH ENHANCEMENT IN ASEAN REGION: A COMPREHENSIVE LITERATURE REVIEW - Abdul Aziz Turaya; Nairobi; Asih Murwiati (ZILLZELL MEDIA PRIMA, 2025)
Financial inclusion has emerged as a pivotal catalyst for sustainable economic development across ASEAN economies. This comprehensive literature review synthesizes findings from 45 peer-reviewed studies published between 2015-2024, examining the nexus between financial inclusion and economic growth in the ASEAN region. Through systematic analysis of existing research, this study identifies key mechanisms through which financial inclusion drives economic expansion, including capital allocation efficiency, entrepreneurship facilitation, and poverty reduction. The review reveals consistent evidence of positive correlation between financial inclusion indicators and GDP growth across ASEAN countries, with digital financial services showing the most pronounced impact. Synthesized findings indicate that countries with higher financial inclusion indices experience 15-25% faster economic growth rates. The study identifies research gaps and proposes future directions for investigating the long-term sustainability of financial inclusion-led growth in emerging economies.